Pediatric Orthopedics: The difficult management of fractures in children (Research, Society and Development, 2022)
Introduction: It is important that the physician is prepared to act in the face of polytrauma in childhood, prioritizing the evaluation and the correct conduct at this time, the care follows the same precepts and dogmas applied to the adult population, protecting the patient's life in the foreground. and maintaining the evaluation of the musculoskeletal system for the next moment, always following the principles of Advanced Trauma Life Support (ATLS). Trauma injuries in children are an important cause of death, especially with children over one year of age. , is the second leading cause of hospitalization in individuals under 15 years of age, with approximately 80% of hospitalizations among adolescents and young adults. Methodology: This is a narrative review of the literature. Results: The data found are in direct agreement with the literature evaluated, as stated by Dimeglio in 1999, whose work found up to 55% of fractures in the age groups from 1 to 11 years. The author comments that up to six years of age, fractures be grouped in 18% of the sample, being found between 06 and 11 years a total of 40% of the fractures. The author highlights the importance of observing that 80% of fractures occurred after the age of six. Also in agreement with the data found, about 65% of fractures occur in patients older than eight years. reports that, among the most common traumatic injuries in childhood, bone fractures are of greatest concern to clinicians, as they cause great Morbi Daddy and permanent sequelae that can affect the child's main joints. A bone fracture can be defined as a discontinuity, which occurs in a bone when force is applied overcoming its elasticity, resulting in this continuity or indirect direct trauma. Fractures in children are more common in males, which are after 10 years of age. In the literature, great challenges were found in the treatment and management of cases of fractures in children, such as their discernment in relation to their clinical situation, making it difficult to adapt and change the child's lifestyle during recovery and the inevitable rest when there is a fracture. Conclusion: In this work it was possible to notice that the bills of Upper limbs present more hospitalization than the lower limbs, which disagrees with the foreign literature in developed countries. This difference in data is linked to the etiology of the trauma, and upper limb injuries involve a defense mechanism mainly against falls, while lower limb injuries are due to traffic accidents. femur fractures, which are the ones with the greatest financial burden and lead to longer hospital stays after surgery.